“Dance Like Nobody’s Watching”: Exploring the Role of Dance-Based Interventions in Perceived Well-Being and Bodily Awareness in People With Parkinson’s - Hadley, Rebecca; Eastwood-Gray, Olivia; Kiddier, Meryl; Rose, Dawn; Ponzo, Sonia (Frontiers in Psychology, 2020)
Evidence indicates bodily perception is negatively related to Parkinson’s disease (PD), in particular people with Parkinson’s (PwP) feel dissatisfaction in their physical abilities and appearance. While established treatments exist to ameliorate motor symptoms in PD, research has yet to explore the effects of wellbeing-focused interventions in relation to the subjective experience of bodily concerns of PwP. This mixed methods exploratory study investigated the constructs of body appreciation in relation to wellbeing in PwP, and the impact of participation in a dance class on these constructs, comparing PwP with age-matched controls. Participants (n = 27 PwP, n = 14 controls) completed the Warwick Edinburgh Mental Wellbeing Scale and the Body Appreciation Scale before and after taking part in a dance class. Wellbeing was positively associated with body appreciation in PwP (rs = 0.64), but not in controls. Following participation in a dance class, all participants’ wellbeing scores increased; a greater increase in wellbeing scores was observed for controls. A pilot qualitative study explored bodily awareness with PwP who attended dance classes (n = 4) and other movement-based activities (n = 4). Analysis of the interview data indicated that PwP who danced showed heightened bodily awareness, including bodily limitations, in comparison with PwP who did not dance. These preliminary findings provide initial insight explaining the lack of improvements in body appreciation in PwP following a dance class. The current study highlights the need for dance interventions for PwP to consider incorporating elements that encourage a body positive attitude alongside fostering perceived wellbeing.